Eksistensi Cadar Ditengah Jilbab Santri - Nurul Inayah; Nawal Ika Susanti (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2019)
The veil is an advanced version of the use of headscarves, in Islamic interpretation studies the arguments governing whether or not the use of veils is still under debate. However, the use of veils is actually in the community, bringing the consequences of rejection greater than the headscarf. Islamic boarding schools in East Java on average do not advocate and ban their santri from wearing veils. This is an interesting thing to be examined more deeply about how the santri still existed in the midst of his friends who were wearing headscarves. The findings in the field about the existence of veiled santri in the Islamic Boarding School Environment are that the first informant (Nur Aina) and the third Informant (Dewi Rahma) can still use the veil as a cover for the Islamic Shari'a wherever the informant is despite being the only veiled santri among santri veiled. While the second informant (Rahmatus Sholehah) could not exist among his friends due to the lack of support from the immediate family, criticism from the people closest to him, and differences in responses within the surrounding community made him unable to stay for Istiqomah using his veil.